THE EFFECTIVENESS OF GROWTH REGULATORS’ FOLIAR APPLICATION ON SUGAR BEET PLANTINGS - Filonenko, S.; Tyshchenko, M.; Raida, V. (Scientific Progress & Innovations, 2022)
The application of growth regulators is an important element of cultivation technologies of field crops including sugar beet. However, these preparations affect crop productivity and the quality of plant products differently. In this connection, studying the peculiarities of sugar beet productivity formation and technological qualities of their roots under specific soil and climatic conditions at foliar application of growth regulators is significant and topical. The purpose of our research was to study the impact of Tecamin Max, Vertex, and Dominant growth regulators at their foliar application on sugar beet productivity and the technological qualities of their roots, to specify the biological peculiarities of root yield formation and their sugar content. For this purpose, it was necessary to solve the following tasks: to study the peculiarities of Bulava sugar beet hybrid plants’ growth and development depending on the application of growth regulators; to find the best growth regulator for foliar application from the studied ones to use on sugar beet plantings depending on the hybrid; to determine the effect of Tecamin Max, Vertex, and Dominant growth regulators on the crop root yield and their technological qualities. The corresponding researches were conducted at Veselopodilska Experimental and Selection Station (Kremenchuk district, Poltava region) of the Institute of Bio-Energy Crops and Sugar Beet of the National Academy of Agrarian Sciences of Ukraine during 2019–2021. As a result of the conducted studies, it has been established that the application of Vertex, Tecamin Max, and Dominant growth regulators on sugar beet plantings has a stabilizing effect on plant density indicators. During the three years, on the average, the number of plants on all the studied variants was the optimal for the corresponding soil and climatic zone – 100 thou/ha (Tecamin Max, 1 l/ha), 93.3 thou/ha (Vertex, 0.5 l/ha), and 91.1 thou/ha (Dominant, 40 ml/ha). Foliar application of the studied growth regulators has a positive impact on leaf-area duration of sugar beet plants. As to this indicator, Tecamin Max growth regulator, applied at a dose of 1 l/ha, was the most effective. After using this preparation, the leaf-area duration on the plot was the largest comparing to other growth regulators. The optimal ratio of different biologically active substances as components of the corresponding growth regulators as well as the correctly chosen doses of their application assisted in activating the photo-synthetic plant activity. As a result, higher yields were obtained on the studied variants with higher sugar content and sugar output. The best results were registered on variant 2, where Tecamin Max growth regulator was foliar applied at a dose of 1 l/ha – 46.3 t/ha, 18 %, and 8.33 t/ha, respectively.